An analysis of the relevant parameter during taking-off of the male long jumpers in China - Ya, L. (Journal of Jilin Institute of Physical Education, 2011)
Taking-off is the most important stage in long jump and its techniques have great impact on the jumpers' performance. Moreover the taking-off techniques are considered the main metewand in long jump. Based on the features of taking-off, this paper makes an analysis of time parameter, speed parameter and angle parameter of the top eight male long jumpers' performance in the 11th National Games and makes a comparison with the former elite long jumpers home and abroad. It aims at finding out the existing problems in taking-off and providing references and basis for the improvement of taking-off techniques and sports level.